LINGUISTIC CRITERIA OF INTENTIONALITY. (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The aim of this paper is to discuss theories that attempt to single out the class of intentional states by appealing to factors that are supposed lycriterial for intentional sentences. The papers starts with distinguishing two issues that arise when one thinks about intentional expressions: the Taxonomy Problem and the Fundamental Demarcation Problem. The former concerns the relation between the classes of distinct intentional verbs and distinct intentional states. The latter concerns the question about how to distinguish intentional states and acts from the non-intentional ones. Next, the general desiderata for theories providing criteria for singling out the class of intentional sentences are in troduced. Finally, distinct proposals for providing such criteria are analyzed. Author argues that neither is satisfactory.